Pembelajaran Tuna Netra SLB Terhadap Media Gambar di SLB Karya Murni Medan - Simanungkalit, Aprianti; Ketaren, Angella; Pardosi, Selma; Tarigan, Sintiya Fransisca Br; Pandia, Pasya Pebina Br; Nahor, Alika Banjar (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
SLB school is a special educational institution designed to meet the needs of children with specialized education needs. Each individual has a unique potential, and SLB comes to providing support and learning that suits their characteristics. (SLB) what is the definition of Extraordinary School and what kind of learning media do you use there to improve the quality of the learning process, of course, Outstanding Education or Extraordinary School (S) is an education for students who have a level of difficulty in following the learning process due to physical, emotional, mental, but have the potential intelligence and talents (7lbs). In Encyclpedia of Disabilitytentang education, it is commonly put forward as follows: "Specialist education, specifically designed construction to meet the unique accompanied of a child with disability". Extraordinary education means that learning is specifically designed to meet the unique needs of children with physical disorders. Every child has a different background of cultural life and developments, and each child may have special needs and different learning obstacles as well as different, so that each child actually requires Education services that are regrettable in line with the learning obstacles and needs of each child, as with children with special needs.